Students’ Perspectives on Translanguaging in Classroom Context - Ninuk Krismanti (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2022)
This study is carried out to investigate students’ perspectives on translanguaging practises in classrooms. The students in this study are fourth semester students of the English Language Education Study Program (ELESP) of STKIP PGRI Banjarmasin. The study is set under qualitative paradigm. The data are collected through questionnaire designed with open-ended questions. The results of the study suggest that students have positive views on translanguaging practices in their classrooms. They believe that the use of Banjarese and Indonesian language in teaching and learning process is not a threat. Instead, it is helpful for lesson understanding and L2 improvement. Moreover, translanguaging increases students’ motivation and gives inspire for their future practices. Translanguaging also helps build good relationship between students and lectures as well as promotes their identities as multilingual speakers. Keywords: translanguaging, perspectives, classroom.